Analisis Tingkat Transfer Pricing, Financial Distress, Pertumbuhan Penjualan, dan Corporate Social Responsibility Terhadap Tax Avoidance - Arianti, Baiq Fitri; Nurkamilah, Halfa (Gorontalo Accounting Journal, 2023)
The purpose of this research is to provide empirical evidence of analysis of the level of transfer pricing, financial distress, sales growth, and corporate social responsibility on tax avoidance. This study uses secondary data from property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021. Determination of the sample in this study using purposive sampling technique. Testing research data using eviews program. The results of this study indicate that transfer pricing, sales growth, and corporate social responsibility have no effect on tax avoidance, while financial distress has a signifikan effect on tax avoidance.